THE DEVELOPMENT OF SMART CIRCUIT MEDIA IN THIRD GRADE MATHEMATICS LEARNING AT MI PLUS AL ISTIGHOTSAH PANGGUNGREJO TULUNGAGUNG - Natasha Nurhaida (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2021)
Abstract: Smart circuits are learning media to be applied in Mathematics learning. This study aims to find out the development process, feasibility, and influence of smart circuit media in mathematics learning for third grade in Elementary School. This study used the Research and Development research method, with the Borg, and Gall model. The development begins with determining the core competencies, basic competencies, indicators and subjects for making questions. The researcher put stickers of interesting cartoon images on each plot on the wooden planks of this medium. The necessary media prerequisites include: dice, pawns, game hints, and a memory. After the media is made, a feasibility test analysis was done, before the t-test. The data collection instruments used questionnaires, observations, and interviews. The results of this study showed that: (1) The smart circuit media is feasible to implemented in improving mathematics learning outcomes. This can be seen from the results of feasibility test by media experts and material experts before it is implemented in the class which showed that the presentation aspect gets a percentage of 82.5% from the first media experts, and 90% from the second media experts; efficiency aspects was 81.25%, and 100%; and media quality aspects was 82.5% and 92.5%. (2) Based on the t-test result, it can be concluded that the smart circuit media can improve student learning outcomes. This is showed by the significant difference in learning outcomes between the experimental class, and the control class with a significance value of 0.014 < 0.05. The impact of this research is the students can understand the material in learning mathematics easily.PENGEMBANGAN MEDIA SIRKUIT PINTAR UNTUK MENINGKATKAN  HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKAAbstrak: Sirkuit pintar adalah media pembelajaran yang menarik untuk diterapkan dalam pembelajaran Matematika. Penelitian ini bertujuan untuk mengetahui proses pengembangan, kelayakan, serta pengaruh media sirkuit pintar dalam pembelajaran matematika kelas III MI. Penelitian ini menggunakan metode penelitian Research and Development, dengan model Borg, and Gall. Pengembangannya dimulai dengan menentukan kompetensi inti, kompetensi dasar, indikator serta mata pelajaran untuk membuat pertanyaan. Peneliti menempelkan stiker gambar kartun yang menarik di setiap petak pada papan kayu media ini. Prasyarat media yang diperlukan antara lain: dadu, bidak, petunjuk permainan, dan bengkel ingatan. Setelah media dibuat, selanjutnya dilakukan analisis uji kelayakan, sebelum dilakukan uji-t. Instrumen pengumpulan data yang digunakan antara lain kuesioner, observasi, dan wawancara. Hasil penelitian ini menunjukkan bahwa: (1) Media sirkuit pintar ini layak digunakan dalam meningkatkan hasil belajar matematika. Hal ini dapat dilihat dari hasil uji kelayakan oleh ahli media, dan ahli materi sebelum diterapkan di lapangan yang menunjukkan bahwa aspek penyajian mendapatkan persentase sebesar 82.5% ahli media pertama, dan 90%  dari ahli media kedua; aspek efisiensi sebesar 81.25%, dan 100%; serta aspek kualitas media sebesar 82.5%, dan 92.5%. (2) Setelah dilakukan uji-t, dapat disimpulkan bahwa media sirkuit pintar dapat meningkatkan hasil belajar peserta didik. Hal ini dibuktikan dengan adanya perbedaan hasil belajar yang signifikan antara kelas eksperimen, dan kelas kontrol dengan nilai signifikansi 0,014 < 0,05. Dampak penelitian ini adalah peserta didik dapat memahami materi pada pembelajaran matematika dengan mudah.